The Challenge of Recruiting Underrepresented Groups – Exploring Organizational Recruitment Practices in Sweden - Osman, Ali; Thunborg, Camilla (Nordic Journal of Working Life Studies, 2019)
The aim of this article is to explore organisational recruitment practices from human resources (HR) experts’ narratives and discuss the challenges of recruiting underrepresented groups in relation to these practices. From the HR experts’ narratives, we identify four organisational recruitment practices: the informal, the pragmatic, the standardised and the strategic. These practices consist of, for example, ‘subjective’ judgements versus ‘objective’ criteria and are construed in relation to different rationalities, which also give rise to various dilemmas in relation to underrepresented groups. From our analysis, there seems to be a paradox between enhancing diversity and counteracting discrimination. Organisational recruitment practices that are counteracting discrimination do not necessarily enhance diversity and recruitment practices that radically work with enhancing diversity can be seen as discriminatory. We thereby draw the conclusion that there is no effective practice for the recruitment of underrepresented groups in the labour market. This is a dilemma for HR experts and a challenge for the Swedish labour market in general.